Alpha Diversity Analysis of Microbiota Dysbiosis in Normal and Colorectal Cancer of Mice Feces - Iqbal, Muhammad; Rivai, M. Iqbal; Suswita, Rini; Irwan, Irwan; Suchitra, Avit (International Journal of Statistics in Medical Research, 2025)
Background: Colorectal cancer development is influenced by both environmental and genetic factors, with the gut microbiota playing a significant role. This research investigates how alterations in gut microbiota are associated with the incidence, progression, prognosis, and early detection of CRC. Methods: An experimental laboratory study was carried out using Sprague Dawley rats that were induced with azoxymethane (AOM) and Dextran Sodium Sulfate (DSS). The thirty rats were divided into three groups: normal, cancer-induced, and treatment. The fecal microbiota profiles were examined through Next Generation Sequencing (NGS), and the data were analyzed for alpha diversity, highlighting the dynamics of the microbial community. Results: The cancer-induced group (K2 Plus) exhibited the highest microbial diversity across Shannon, Simpson, Chao1, and PD Whole Tree indices, while the treatment group (P2 Plus) demonstrated the lowest. Conclusion: These findings suggest that the increase in diversity observed in cancer-induced mice reflects disruption of community stability and blooming of pathobionts. Conversely, treatment with Lactococcus lactis D4 reduced diversity, potentially by selectively suppressing pro-inflammatory or pathogenic taxa, indicating a beneficial probiotic effect in mitigating dysbiosis associated with colorectal cancer.